2022
DOI: 10.1371/journal.pgph.0000776
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and willingness to use HIV oral pre-exposure prophylaxis among people who inject drugs in Dar es Salaam, Tanzania: A cross-sectional survey

Abstract: People who inject drugs (PWID) are at increased risk of HIV infection. Pre-exposure prophylaxis (PrEP) could help in HIV prevention among PWIDs. However, little is known about PrEP use among PWIDs in low and middle-income countries. This study reports the awareness of and willingness to use PrEP and the associated factors among PWID in Tanzania. A cross-sectional survey was conducted using respondent-driven sampling (RDS) to recruit PWIDs in Dar es Salaam, Tanzania. Data were collected using an interviewer-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Integrating oral PrEP services into other services may be cost-effective, considering that some of the infrastructure will already be in place. Furthermore, fewer HCWs may be required compared to when the services are offered separately ( 8 ). In addition, providing oral PrEP in a range of routine settings may help reduce the stigma associated with specialized clinics and HIV services ( 26 ).…”
Section: Strategies To Address the Barriers To Oral Prep Use Among Pwidmentioning
confidence: 99%
See 3 more Smart Citations
“…Integrating oral PrEP services into other services may be cost-effective, considering that some of the infrastructure will already be in place. Furthermore, fewer HCWs may be required compared to when the services are offered separately ( 8 ). In addition, providing oral PrEP in a range of routine settings may help reduce the stigma associated with specialized clinics and HIV services ( 26 ).…”
Section: Strategies To Address the Barriers To Oral Prep Use Among Pwidmentioning
confidence: 99%
“…A study conducted in Tanzania revealed that 71.4% of the participants were willing to use oral PrEP if it was made available to them ( 8 ). Factors that were associated with the willingness to use oral PrEP in the study were the risk of HIV infection, the frequency of condomless sex, the number of sexual partners, and being in an HIV prevention program ( 8 ). Another study conducted in India revealed a 52.4% willingness to use oral PrEP among participants ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations